Operational and economic performance of coffee harvest using lateral harvesters - Silva, Fábio Moreira da; Oliveira, Ezequiel de; Guimarães, Rubens José; Figueiredo, Carlos Augusto Pereira de; Silva, Flávio Castro da (Coffee Science - ISSN 1984-3909, 2007)
Coffee harvest (Coffea arabica L.) is an expensive process that demands high costs with labor, increasingly scarce in its various stages: cleaning under coffee tree canopy, harvest, sweeping , gathering, fanning and transport. Harvesting is the removal of grains from the plant, a stage where mechanization augment constantly. Mechanical harvesting does not remove all grains from the plant and a complementary hand-picking process is necessary, being important to analyse mechanical and manual harvest to know the minimum cost of the overall operation. This work analyses harvesting costs with mechanical harvest machines together with manual harvesting, based upon performance of a lateral harvester at three harvesting times. The project was carried out under 2003 field harvesting conditions, in Morro Alto farm, located in Neponuceno- MG, Brazil in a 6-year old Acaiá coffee variety crop planted in a 3.0 x 1.0 meters spacing, plants 2.7 meters in height. Tests were accomplished in plots at random with three replicates, each one with 5 plants in line, using a lateral harvester Dragão Versati model, connected to and pulled by a Valmet 785 tractor with 4-wheel drive and reduccion gear for speed. Treatments consisted of interaction of the following variables: stage of maturation of the fruits, vibration frequency and operational speed of the harvester. Results indicate that harvesting at the intermediate time of harvesting, when 10-15% grains are still green, was more adequate, with 80.3% efficiency in harvesting and 37% less costly than in manual harvesting.